Contribution to the knowledge of the Anthidulum Michener and Ctenanthidium Urban (Hymenoptera, Apidae) with new species from Argentina and Peru - Parizotto, Daniele R.; Urban, Danúncia (Zootaxa, 2013)
Updated diagnostic generic characters for the neotropical anthidiine genera Anthidulum and Ctenanthidium are presented. Ctenanthidium versicolor sp. nov. from Argentina and Anthidulum rozeni sp. nov. from Peru are described, illustrated and distinguished from their congeners. A key to the species of Ctenanthidium is provided. The male of Ctenanthidium nigripes Urban, 1993 is described for the first time.